Nursing oral suction intervention to reduce aspiration and ventilator events (NO‐ASPIRATE): A randomized clinical trial. (23rd January 2019) - Sole, Mary Lou; Talbert, Steven; Yan, Xin; Penoyer, Daleen; Mehta, Devendra; Bennett, Melody; Middleton, Aurea; Emery, Kimberly Paige
Abstract: Aim: The primary aim of this study is to compare an oropharyngeal suction intervention versus usual care on microaspiration in intubated patients. Secondary aims are to evaluate the intervention on ventilator‐associated condition rates, time to occurrence and compare tracheal‐oral α‐amylase ratios between groups. Design: Prospective randomized clinical trial. Methods: The study received funding from the National Institutes of Health in February 2014 and Institutional Review Board approval in July 2013. Over 4 years, a convenience sample of 600 orally intubated, ventilated adult patients will be enrolled within 24 hr of intubation. The target sample is 400 participants randomized to the two groups. The intervention involves enhanced suctioning of the mouth and oropharynx every 4 hr, while the usual care group receives a sham suctioning. The research team will deliver usual oral care to all patients every 4 hr and collect oral and tracheal specimens every 12 hr, to quantify α‐amylase levels to detect aspiration of oral secretions. Study completers must be enrolled at least 36 hr (baseline and three paired samples). Outcomes include α‐amylase levels, percent of positive specimens, ventilator‐associated conditions, length of stay, ventilator hours, and discharge disposition. Discussion: Enrolment has closed, and data analysis has begun. Subgroup analyses emerged, contributing to future research knowledge. Impact: Standardized interventions have reduced but do not address all risk factors associated with ventilator‐associated conditions. This study provides the potential to reduce microaspiration and associated sequelae in critically ill, intubated patients. Abstract : 目的: 本研究的主要目的是比较口咽吸入干预与常规护理对插管患者微抽吸的影响。次要目标是评价对通风机检测相关条件, 发生时间的干预, 比较气管口服α淀粉酶团体之间的比率。 设计: 前瞻性随机临床试验。 方法: 该研究于2014年2月获得了美国国立卫生研究院的资助, 并于2013年7月获得了机构审查委员会的批准。在4年内, 600例经口插管、通气的成年患者的便利样本将在插管后24小时内登记。目标样本是随机分为两组的400名参与者。干预包括每4小时加强口腔和口咽部的吸痰, 而通常的护理组接受假吸痰。研究小组将提供常规口腔护理, 所有患者每4小时和收集口腔气管标本每12小时, 量化α淀粉酶水平来检测口腔分泌物的吸出情况 研究完成者必须至少登记36小时(基线和三个配对样本)。 结果包括α淀粉酶水平, 阳性样本的百分比, 呼吸机相关情况, 住院时间、呼吸机工作时间和出院情况。 讨论: 登记已经结束, 数据分析已经开始。亚组分析出现, 有助于未来的研究。 影响: 标准化的干预措施已经减少, 但并没有解决与呼吸机相关条件相关的所有风险因素。这项研究为减少危重症插管患者的微吸入性和相关后遗症提供了可能。